2013
DOI: 10.1126/science.1233866
|View full text |Cite
|
Sign up to set email alerts
|

ESCRT-III Assembly and Cytokinetic Abscission Are Induced by Tension Release in the Intercellular Bridge

Abstract: The last step of cell division, cytokinesis, produces two daughter cells that remain connected by an intercellular bridge. This state often represents the longest stage of the division process. Severing the bridge (abscission) requires a well-described series of molecular events, but the trigger for abscission remains unknown. We found that pulling forces exerted by daughter cells on the intercellular bridge appear to regulate abscission. Counterintuitively, these forces prolonged connection, whereas a release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
198
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(215 citation statements)
references
References 48 publications
13
198
0
2
Order By: Relevance
“…Among the four multi-subunit protein complexes (ESCRT 0-I-II-III), extensive studies reported the fundamental role of ESCRT-III in abscission (Capalbo et al, 2016;Carlton et al, 2012;Carlton and Martin-Serrano, 2007;Eikenes et al, 2015;Lafaurie-Janvore et al, 2013;Morita et al, 2007). ESCRT-III becomes enriched at the midbody, an organelle at the intercellular bridge, which acts as a platform for the recruitment and organisation of various proteins involved in both the control and execution of the abscission process.…”
Section: Escrt and Ptdins3p: Potential Connections And Future Directimentioning
confidence: 99%
“…Among the four multi-subunit protein complexes (ESCRT 0-I-II-III), extensive studies reported the fundamental role of ESCRT-III in abscission (Capalbo et al, 2016;Carlton et al, 2012;Carlton and Martin-Serrano, 2007;Eikenes et al, 2015;Lafaurie-Janvore et al, 2013;Morita et al, 2007). ESCRT-III becomes enriched at the midbody, an organelle at the intercellular bridge, which acts as a platform for the recruitment and organisation of various proteins involved in both the control and execution of the abscission process.…”
Section: Escrt and Ptdins3p: Potential Connections And Future Directimentioning
confidence: 99%
“…Dans le cadre d'un travail récemment publié dans Science [10], nous avons souhaité étudier les facteurs environnementaux qui pourraient retarder ou induire l'abscission des cellules. Nous nous sommes intéressés en particulier au rôle des forces de traction exercées irréversible puisqu'aucun retour en arrière n'est possible une fois le pont coupé.…”
Section: La Régulation De L'abscission Par La Tension Entre Cellules unclassified
“…Some variability might be due to the variable rate of daughter cell spreading that exerts tension on the intercellular bridge. Counterintuitively, increased tension on the bridge induces a delay in abscission (Lafaurie-Janvore et al 2013 Figure 4. Abscission in metazoa.…”
Section: Regulation Of Abscissionmentioning
confidence: 99%